KINERJA GURU SEKOLAH DASAR NEGERI KECAMATAN SEMIDANG ALAS MARAS KABUPATEN SELUMA - Adisel Adisel (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
This study aims to analyze the performance of State Elementary School teachers in Semidang Alas Maras District, Seluma Regency, Bengkulu Province and the factors that influence it. The population and sample in this study were all elementary school teachers in Semidang Alas Maras District, Seluma Regency, Bengkulu Province, totaling 161 people. Data collection techniques using questionnaires and data analysis using multiple linear regression. The results of this study prove that the performance of teachers is in the good category and there is a positive and significant influence between the variables of intellectual, emotional and spiritual intelligence on the performance of the teachers at the Semidang Alas Maras Public Elementary School, Seluma Regency, Bengkulu Province. Keyword: Intellectual Intelligence, Emotional, Spiritual. Teacher Performance